Light scattering studies of irregularly shaped particles - Heinson, Yuli Wang (Kansas State University, 2016)
We present light scattering studies of irregularly shaped particles which significantly affect the climate. We built and calibrated our apparatus which was able to measure all six independent scattering matrix elements. Our apparatus detects light from 0.32° to 157° simultaneously. We studied all six scattering matrix elements of irregularly shaped Arizona Road Dust which behave differently than those of spheres. We strongly focused on the most important scattering matrix element – the phase function, scattered intensity vs. the scattering angle, which we applied Q-space analysis to. Q-space analysis involves plotting the scattering intensity vs. the magnitude of the scattering wave vector q or qR with R the radius of a particle, on a double logarithmic scale. We measured and studied the phase functions of Al₂O₃ abrasives; compared the scattering from the abrasives with the scattering of spheres. To generalize the study, we collected a large amount of experimental and theoretical data from our group and others and applied Q-space analysis. They all displayed a common scattering pattern. The power law exponents showed a quasi-universal functionality with the internal coupling parameter ρ'. In situ studies of the soot fractal aggregates produced from a burner were also conducted. A power law exponent -1.85 is seen to imply the aggregates have fractal dimension of D[subscript f]=1.85. The overall work presented shows Q-space analysis uncovers patterns common to all particles: a q-independent forward scattering regime is followed by a Guinier regime, a power law regime, and sometimes an enhanced back scattering regime. The description of the patterns applies to spheres as well, except the power law regime has more than a single power law. These simple patterns give a unified description for all particle shapes. Moreover, the power law exponents have a quasi-universal functionality with ρ' for non-fractal aggregates. The absolute value of the exponents start from 4 when ρ' is small. As ρ' increases, the exponents decrease until the trend levels off at ρ'≳10 where the exponents reach a constant 1.75±0.25. All the non-fractal particles fall on the same trend regardless of the detail of their structure.
Keywords: Light scattering; Q-space analysis; Guinier analysis; Irregular Shapes; Universal behavior